The effect of light supply on microalgal growth, CO2 uptake and nutrient removal from wastewater - Goncalves, AL (2014)
Microalgal based biofuels have been reported as an attractive alternative for fossil fuels, since they constitute a renewable energy source that reduces greenhouse gas emissions to the atmosphere. However, producing biofuels from microalgae is still not economically viable. Therefore, the integration of biofuel production with other microalgal applications, such as CO2 capture and nutrient removal from wastewaters, would reduce the microalgal production costs (and the environmental impact of cultures), increasing the economic viability of the whole process. Additionally, producing biofuels from microalgae strongly depends on microalgal strain and culture conditions. This study evaluates the effect of culture conditions, namely light irradiance (36, 60, 120 and 180 mu E m(-2) s(-1)) and light:dark ratio (10:14, 14:10 and 24:0), on microalgal growth, atmospheric CO2 uptake and nutrient (nitrogen and phosphorous) removal from culture medium. Four different microalgal strains, Chlorella vulgaris, Pseudokirchneriella subcapitata, Synechocystis sauna and Microcystis aeruginosa, were studied to ascertain the most advantageous regarding the referred applications. This study has shown that higher light irradiance values and light periods resulted in higher specific growth rates and CO2 uptake rates. C vulgaris presented the highest specific growth rate and CO2 uptake rate: 1.190 +/- 0.041 d(-1) and 0.471 +/- 0.047 gam L-1 d(-1), respectively. All the strains have shown high nitrogen removal efficiencies, reaching 100% removal percentages in cultures with higher light supply. Phosphorus removal increased with light irradiance and with light:dark ratio. The highest removal efficiency, 67.6 +/- 7.1%, was achieved by the microalga C vulgaris.